FORMULATION OF ANTIOXIDANT GEL FROM STANDARDIZED GREEN CINCAU (CYCLEA BARBATA L. MIERS) ETHANOLIC EXTRACT - GANGGA, ERLINDHA; FARIDA, YUNAHARA; KARTININGSIH (International Journal of Applied Pharmaceutics, 2020)
Objective: The aim of this study to develop an antioxidant gel from standardized green cincau (Cyclea barbata L. Miers) ethanolic extracts. Methods: The standardized extract of green cincau (Cyclea barbata L. Miers) ethanolic extracts were formulated as active ingredients of antioxidant gel. The dried leaf of Cyclea barbata L Miers was extracted with ethanol 70%. The extract was analyzed its phytochemical screening and antioxidant activity with DPPH methods. The extract was used as active ingredients of antioxidant gel. The gels were evaluated physically and chemically, such as organoleptic test, homogeneity, viscosity and rheology, spreadability, pH test, antioxidant activity, and analysis of microbial contamination test. Results: The results showed that all formulas were greenish-yellow and have homogeneous, the viscosity of 14267-45533 cps, spreadability of gels 1783.8–6631.5 mm2, pH value of 4.57–5.74, and analysis of microbial contamination has colonies not more than 103 colonies/g or colonies/ml. Statistical analysis used two ways ANOVA to investigate gels time and temperature effects toward gel preparations stability. There was no effect on the viscosity, spreadability, and pH tests, on the all formula with P>0.05. The antioxidant activity of the formula showed that all formulas changed after 3 mo of storage at 40 °C. Formula II had stronger antioxidant activity than the others with an IC50 value of 57.60µg/ml. Conclusion: All formulas showed fairly strong antioxidant activity because it can inhibit the activity of free radicals that could inhibit the premature aging of the skin.